Pengembangan Media Komik Digital Matematika Berbasis Kontekstual Materi Bangun Datar untuk Kelas IV - Alfiani Zulfa, Isna Fitria; Mardiati, Asih (Jurnal Didaktika Pendidikan Dasar, 2025)
Student learning outcomes in mathematics subjects, on average, only reach the KKM limit. Students’ understanding remains abstract; the material presented is not well-received; and there is a lack of concrete media. This research was conducted to determine the level of feasibility of digital comic media products for mathematics based on contextual flat material for 4th-grade elementary school students. The material presented concerns regular and irregular polygons. This media was developed in the form of a Flipbook. The development model used is the 4D development model. This research used limited trials across three phases: individual, small-group, and field. The results of the assessment were 90% for media experts, 92.5% for material experts, 78.3% for learning experts, and 87.5% for linguists. The teacher’s response assessment was 93%, while the students’ response at the individual trial stage was 91.6%. In the small group experiment, the result was 95.1%, while in the field test stage, it was 96.5%. In conclusion, this medium is suitable for use.